The heat shock protein 70 inhibitor VER155008 suppresses the expression of HSP27, HOP and HSP90β and the androgen receptor, induces apoptosis, and attenuates prostate cancer cell growth. Issue 1 (21st June 2019) - Brünnert, Daniela; Langer, Clara; Zimmermann, Luise; Bargou, Ralf C.; Burchardt, Martin; Chatterjee, Manik; Stope, Matthias B.
Abstract: Heat shock proteins (HSPs) are molecular chaperones that play a pivotal role in correct folding, stabilization and intracellular transport of many client proteins including those involved in oncogenesis. HSP70, which is frequently overexpressed in prostate cancer (PCa), has been shown to critically contribute to tumor cell survival, and might therefore represent a potential therapeutic target. We treated both the androgen receptor (AR)‐positive LNCaP and the AR‐negative PC‐3 cell lines with the pharmacologic HSP70 inhibitor VER155008. Although we observed antiproliferative effects and induction of apoptosis upon HSP70 inhibition, the apoptotic effect was more pronounced in AR‐positive LNCaP cells. In addition, VER155008 treatment induced G1 cell cycle arrest in LNCaP cells and decreased AR expression. Further analysis of the HSP system by Western blot analysis revealed that expression of HSP27, HOP and HSP90β was significantly inhibited by VER155008 treatment, whereas the HSP40, HSP60, and HSP90α expression remained unchanged. Taken together, VER155008 might serve as a novel therapeutic option in PCa patients independent of the AR expression status. Abstract : We could demonstrate antitumor activity of the HSP70 inhibitor VER155008 in both AR‐positive and ‐negative prostate cancer cell lines by inhibiting proliferation and inducing apoptosis in a low micromolar range. In addition, VER155008 induced a distinct diminishing of HSP27, HOP and HSP90α expression, whereas the expression of HSP40, HSP60, HSP90βta, and HSP70 itself was not altered. VER155008 treatment also led to suppression of the AR and might represent a promising therapeutic agent for prostate cancer.